Design & Analysis of S-Band Right Hand Circularly Polarized Conical Horn Antenna for NavIC Receiver - N, Likith; K M, Gayathri; S, Thusshara; Sanjeetha, Maria; N, Thangadurai (International Journal of Engineering and Technology, 2018)
In satellite communication systems the horn antennas are being used widely due to its robustness and capable to operate at frequencies which are very high. Here, the right hand circular polarized conical horn antenna is designed for S-band NavIC receiver. The waveguides and conical horn antenna dimensions are designed by using standard formulas and after that they are given to a simulation tool for the S band frequency. The performance parameters like return loss, radiation pattern, gain and directivity are considered for further analysis. In the circular waveguide from the TE11 mode conical horn antenna is to be designed into high gain and a good VSWR.Â Â